ADOC/ADOC-S導入後の訪問作業療法に関する記述的研究—ケースシリーズ - 米嶋 一善; 齋藤 佑樹; 友利 幸之介 (作業療法, 2024)
要旨：訪問作業療法の対象者に，作業選択意思決定支援ソフト（ADOC）/ADOC学校版（ADOC-S）の導入を試み，その導入率，導入可能／不可能な事例の特徴，経時的な支援内容，客観的変化について検討した．ADOC/ADOC-Sが導入可能であった割合は30名中11名（36.7％）で，目標は，活動と参加に焦点が当たったものとなったが，ADOCを使用後もSMARTの視点でより具体化することが必要であった．目標の達成までには，目標調整や再設定などさまざまな対応が必要であった．介入後には，目標の遂行度・満足度以外にも，健康関連QOLや作業を基盤としたアウトカムでもポジティブな変化が認められた． 　We attempted to introduce the Aid for Decision-making in Occupational Choice (ADOC) and ADOC for schools (ADOC-S) to clients receiving home-based occupational therapy. Our study examined the acceptance rate, characteristics of clients where acceptance was possible or not possible, the content of longitudinal intervention, and subjective and objective outcome changes. Out of the 30 clients included in the study, 11 clients (36.7%) successfully accepted ADOC/ADOC-S. The focus of the goals shifted towards activities and participation. However, even after implementing ADOC, further specification using the SMART framework was found to be necessary. Various adjustments and goal re-evaluations were required to achieve the desired outcomes. Following the intervention, positive changes were observed not only in the degree of goal attainment and satisfaction, but also in terms of health-related quality of life and outcomes based on occupational performance.